2017
DOI: 10.18632/oncotarget.21157
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein A-I mimetic peptide 4F suppresses tumor-associated macrophages and pancreatic cancer progression

Abstract: Pancreatic cancer is an aggressive malignancy that is unresponsive to conventional radiation and chemotherapy. Therefore, development of novel immune therapeutic strategies is urgently needed. L-4F, an Apolipoprotein A-I (ApoA-I) mimetic peptide, is engineered to mimic the anti-inflammatory and anti-oxidative functionalities of ApoA-I. In this work, H7 cells were orthotopically implanted in C57BL/6 mice and treated with L-4F. Then, pancreatic cancer progression and the inflammatory microenvironment were invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 49 publications
2
27
0
Order By: Relevance
“…ApoA1, a major protein component of the HDL complex, is involved in "reverse cholesterol transport" by transporting excess cholesterol from peripheral cells back to the liver for excretion. Besides, ApoA1 has an anti-in ammatory characteristic [12], suggest its role in the in ammatory diseases. Previous studies have revealed that serum ApoA1 was associated with the outcome of patients with sepsis and acute respiratory distress syndrome induced by pneumonia, as well as critically ill patients [13][14][15][16].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…ApoA1, a major protein component of the HDL complex, is involved in "reverse cholesterol transport" by transporting excess cholesterol from peripheral cells back to the liver for excretion. Besides, ApoA1 has an anti-in ammatory characteristic [12], suggest its role in the in ammatory diseases. Previous studies have revealed that serum ApoA1 was associated with the outcome of patients with sepsis and acute respiratory distress syndrome induced by pneumonia, as well as critically ill patients [13][14][15][16].…”
Section: Discussionmentioning
confidence: 98%
“…ApoA1 and its mimetic peptide D-amino acids (D-4F) exhibit therapeutic potential in treating cancer, in uenza, sepsis and a variety of lung diseases, such as acute respiratory distress syndrome (ARDS), mainly due to its anti-in ammatory, anti-oxidant and anti-apoptotic properties [12,[20][21][22][23]. In addition, it is noteworthy that ApoA1 inhibits IL-6 release and reduces macrophage activation [21].…”
Section: Discussionmentioning
confidence: 99%
“…First, apoA1 has been proved to negatively alter tumor-permissive features of tumor microenvironment through multiple pathways. These pathways include but are not limited to the following: suppressing the increase in myeloid-derived suppressor cells to decrease tumor volume [51]; reducing the matrix metalloproteinase-9 protein level and activity to inhibit tumor metastasis [52]; increasing the recruitments of tumor cell killing macrophages and CD8 T cells [53]; reducing the level of surviving, a anti-apoptotic protein, responsible for tumor regression [54]. Second, apoA1 and apoA1 mimetic peptides can bind pro-inflammatory or pro-angiogenic phospholipids, such as lysophosphatidic acid.…”
Section: Discussionmentioning
confidence: 99%
“…APOA1 mimetic peptides are 18‐amino acid sequences that recapitulate the secondary structure and partial function of APOA1 . APOA1 mimetic peptides were found to inhibit the development of ovarian cancer, breast cancer, colon cancer, and pancreatic cancer both in vitro and in vivo. APOA1 itself could also exert a suppressive effect on ovarian cancer .…”
Section: Apolipoproteins and Cancermentioning
confidence: 99%